2020
DOI: 10.1177/1369433220912350
|View full text |Cite
|
Sign up to set email alerts
|

Seismic fragility analysis of two-story ultra-high ductile cementitious composites frame without steel reinforcement

Abstract: This article numerically studies the seismic vulnerability of the frame structure made of ultra-high ductile cementitious composites without longitudinal and transverse reinforcement. A non-linear finite element model is established with the help of Open System for Earthquake Engineering Simulation and calibrated by shaking table test results on an ultra-high ductile cementitious composite-RC frame whose seismic vulnerable parts were replaced by ultra-high ductile cementitious composites without steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Yu et al [22][24] developed a new-type of ECC that offers a superior tensile strain capacity (i.e., more than 5%), called ultra-high ductile cementitious composites (UHDCC). Experimental and analysis results showed that UHDCC can effectively strengthen reinforced concrete structures [25] [26]. The application of UHDCC to strengthen multi-storey unreinforced masonry structures is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [22][24] developed a new-type of ECC that offers a superior tensile strain capacity (i.e., more than 5%), called ultra-high ductile cementitious composites (UHDCC). Experimental and analysis results showed that UHDCC can effectively strengthen reinforced concrete structures [25] [26]. The application of UHDCC to strengthen multi-storey unreinforced masonry structures is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic evaluation and fragility analysis of various RC structures have been the main objective of many studies, yet the inclusion of vertical ground shaking has not been usually considered (Anwar et al, 2020; Boushehri et al, 2020b; Dong et al, 2020; Fang et al, 2018; Farsangi et al, 2014; Hashmi and Madan, 2020; Sfahani et al, 2015; Tafti et al, 2020). Besides, studies have been done on the site response analysis and soil-structure interactions, yet mostly the horizontal excitations have been taken into account (Boushehri et al, 2020a; Zogh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%